Risk-based approach to food safety research: Application to pork value chains in Vietnam - Hung Nguyen-Viet; Sinh Dang Xuan; Tran Thi Tuyet Hanh; Phuc Pham Duc; Grace, Delia; Unger, Fred; Makita, K. (International Livestock Research Institute, 2015)
Introduction: Food-borne disease is a major public health issue in Vietnam. The contamination of popular foods can occur all along the food value chains. It is important to understand how and where food safety issues arise in order to mitigate and prevent food-borne diseases. Risk-based approach is a tool for managing food safety, however in Vietnam it is rarely applied and the capacity for application is still lacking. This paper describes how food safety risk assessment research has been applied for the pork value chain in Vietnam. Methods: We have conducted a risk assessment research to assess health risks related to pork consumption in the context of pig smallholder value chains and pork traded in informal markets. We collected 216 samples from 72 pig farms (floor swab, drinking and waste water), 545 samples from 49 slaughterhouses (carcass swab, lymph node, rectal feces, floor swab and washing water) and 514 samples from 220 pork retailed shops at informal markets (pork cuts, ground pork and cutting board swab) in Hung Yen and Nghe An provinces in the north and central of Vietnam. These 1275 samples were analyzed to detect qualitatively and quantitatively for Salmonella and E. coli. Chemical hazards (antibiotic, growth promoters, and heavy metal residues) in 190 pork samples from informal markets were also analyzed. Pork consumption behavior and cross-contamination modalities during pork preparation were assessed. Findings and interpretations: Overall prevalence of Salmonella combined from all types of above mentioned samples at pig farms, slaughterhouses and pork shops were 35%, 30% and 37%, respectively. Salmonella contamination in the final product (pork at market) was 45% and an average concentration of 9 MPN/g was recorded. E. coli average loads along different points of the chain were 5.3±1.4 (farm floor swabs), 2.9±0.9 (carcass swabs), 3.1±1.0 (slaughterhouse floor swabs), and 3.3±1.1 (market shop cutting board swabs) logCFU/cm2 , whereas pork from market had 3.4±0.9 logCFU/g. Demonstrated high levels of Salmonella in the final product (pork at market) induces the potential health risks for the consumers. High values for E. coli indicates general poor hygiene along the chain. 50% and 16.7% pooled samples were positive with sulfamethazine and chloramphenicol, with average residue levels of 156 µg/kg and 0.54 µg/kg, respectively. A quantitative risk model is being developed and integrates information on contamination along the pork value chain to characterize the health risk caused by Salmonella. Appropriate hygiene practices and management are required to achieve better pork quality and reduce the risk for the consumers.